2012
DOI: 10.1002/app.38292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the influence of polyoxide‐based surfactants on the separation process of model emulsions of asphaltenes using the FTIR‐ATR technique

Abstract: During extraction of crude oil, water is generally present in the oil. This water-in-oil (w/o) mixture undergoes turbulent flow that promotes sheer forces, resulting in the appearance of emulsions. These emulsions can be highly stable due to the presence of compounds with polar characteristics such as asphaltenes, which act as natural emulsifiers and form resistant films at the oil-water interface. Nonionic surfactants based on polyoxides are widely used to prevent the formation or to break down w/o emulsions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…They suggested that the flocculation when using PoAC works by electrostatic charge neutralization and bridging, while PEI works by demulsification. They also cited the results of Aguiar and collaborators showing that copolymers containing ethylene oxide and propylene can be used as demulsifiers of water-in-oil emulsions and can displace asphaltenes, which are natural surfactants (Aguiar et al, 2013). Based on these findings and also on the results of variation of the interfacial tension and interfacial dilational modulus with temperature, the authors concluded that PEI works by demulsification (Zhang et al, 2015).…”
Section: Gao Et Al (2011)mentioning
confidence: 94%
“…They suggested that the flocculation when using PoAC works by electrostatic charge neutralization and bridging, while PEI works by demulsification. They also cited the results of Aguiar and collaborators showing that copolymers containing ethylene oxide and propylene can be used as demulsifiers of water-in-oil emulsions and can displace asphaltenes, which are natural surfactants (Aguiar et al, 2013). Based on these findings and also on the results of variation of the interfacial tension and interfacial dilational modulus with temperature, the authors concluded that PEI works by demulsification (Zhang et al, 2015).…”
Section: Gao Et Al (2011)mentioning
confidence: 94%